Enlargement of the left atrium is associated with increased infiltration of immune cells in patients with atrial fibrillation who had undergone surgery. Issue 2 (23rd August 2014) - Yamashita, Takeshi; Sekiguchi, Akiko; Suzuki, Shinya; Ohtsuka, Takayuki; Sagara, Koichi; Tanabe, Hiroaki; Kunihara, Takashi; Sawada, Hitoshi; Aizawa, Tadanori
Abstract: Background: Enlargement of the left atrium (LA) is a risk factor of atrial fibrillation (AF) recurrence after pharmacological and nonpharmacological interventions for AF. However, structural changes associated with LA enlargement have not been fully elucidated. Methods: To examine inflammation in the structural changes associated with LA enlargement, human left appendages obtained from 27 patients who underwent cardiac surgery by using the maze procedure were subjected to immunohistochemical analysis. Results: The extent of interstitial fibrosis increased according to the increase in LA dimension (LAD) as assessed by using ultrasound echocardiography. The extent of the infiltration of CD68‐positive macrophages and CD3‐positive T cells increased simultaneously according to the increments in LAD. The areas infiltrated by immune cells were positively and significantly correlated with LAD ( r 2 =0.58, p <0.01 for CD68; r 2 =0.49, p <0.01 for CD3). Conclusions: In the patients with AF, LA enlargement was associated not only with the increase in the extent of interstitial fibrosis but also with the changes in the LA component cells, including an increase in number of immune cells resident in tissues.